Modelling, control and investigation of an HVDC transmission for an offshore wind farm - Kahinpour, Bahman (My University, 2009)
The aim of this report is to introduce the concept of a centralized control strategy for an offshore wind farm and demonstrate it as an interesting solution for the offshore wind farms through showing its feasibility, analyzing its advantages and evaluating it from an energy production point of view. In this thesis work, first of all, a model of the wind turbine including the induction generator, the non-stiff shaft with a gear-box and the wind energy conversion is derived and is implemented in MATLAB/Simulink and PSCAD/EMTDC. In the next step, a control strategy based on the induction machine V/Hz control principles is derived which is aimed to maximize the aerodynamic conversion efficiency through setting an appropriate frequency for the offshore wind farm and also to minimize the induction generator and the transformer losses through setting an appropriate voltage level for the offshore wind farm. The latter case involves decreasing the fluxes in the generators and the transformers of the wind turbines at low wind speeds in order to decrease the losses in the cores of the wind turbine generators and transformers. The derived strategy is also implemented in the both simulation software and verified. The mentioned loss minimization feature is derived with expandability in mind so that it may be a base for the future work and also may be applied in systems not related to the wind systems. The convergence of the nonlinear centralized speed control algorithm is shown in MATLAB and the effectiveness of the derived control strategy in controlling the flux and the speed is demonstrated. In addition, the losses due to the removal of an individual control system in each wind turbine is also calculated and shown as percentage of the annual wind farm production. In the end of the report, it is concluded that in the offshore wind farms where an HVDC transmission is used, it is possible to remove the individual control systems along with the corresponding converters and replace them with a single larger converter in the HVDC station. In this case, a more advanced control strategy should be used for controlling the converter in the HVDC station. In this thesis work, it is shown that it is possible to derive a centralized control strategy. The control strategy that the controller follows should involve the maximization of the energy absorbed from the wind by the wind turbines through setting the correct reference grid frequency and thus the correct reference rotational speed for the whole wind farm and also compensate for the slip so that the aerodynamic efficiencies become maximum and also may involve minimizing the lost energy by increasing the efficiencies through setting the correct reference voltage level. It is shown in this work that the energy input to the wind turbine can be maximized by setting a correct rotational speed as the reference and the lost energy in the system can be minimized by lowering the flux magnitude at low wind speeds. It is also shown that in addition to being feasible, the percentage of the annual lost energy due to using this centralized strategy is less than 2% in the worst case and moreover such losses decrease in the areas where the wind is less gusty.
Keywords: Elkraftteknik; Electric power engineering